The voice of the cypresses: Cyrus Cassells and the poetry of Salvador Espriu - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Dídac Llorens Cubedo Universidad Nacional de Educación a Distancia (UNED), Spain   ABSTRACT "To the cypress again and again" is Cyrus Cassells's poetic response to the work of Salvador Espriu, a poet whose reception has been limited by his belonging to a minority culture and his commitment to the Catalan language. In its first eight sections, the poem reads as a dramatic monologue: its author adopts Espriu's voice, successfully evoking his poetic world. In what could be considered the second part of the poem, a different poetic speaker  identifiable with Cassells  shares personal memories of Espriu: the man, his nation and his culture. At the end of the poem, the emblematic cypresses are identified with the Catalan people and their voice is heard. The poem is an example of epistolary elegy, a mode that allows Cassells to enter into dialogue with deceased personalities who have had artistic or historical relevance. In so doing, the American poet shows, like Espriu did, an acute sense of cultural tradition.